HERITABILITY AND HETEROSIS OF GRAIN YIELD ON DOWNY MILDEW RESISTANCE (DMR) AND QUALITY PROTEIN MAIZE (QPM) INBREDS AND THEIR SINGLE CROSS HYBRIDS - D. Ruswandi; N. Wicaksana; M. Rachmadi; A. Ismail; D. Arief; F. Kasim (Zuriat, 2005)
Improvement of high yield maize cultivars possessing high quality of seed as showed by high lysine and tryptophan content must be fulfilled with resistance against downy mildew pathogen in any maize breeding program. A set of experiment to study genetic variability and to estimate both heritability and heterosis of important characters of grain yield on DMR and QPM lines has been conducted. Four downy mildew resistance (DMR) lines, i.e. Nei 9008, P 345, Ki 3, and MR 10; three quality protein maize (QPM) lines, including CML 161, CML 163, and CML 172; and their single cross hybrids formed based on line × tester mating design were used in the experiment. The following characters: height of the first ear, seeds number per row, seed weight per ear, and grain yield per plot showed broad genetic variability. Narrow sense heritability (hns) of grain yield and its components ranged from 0.01 to 0.71. Broad sense heritability (hbs), on the other hand, ranged from 0.20 to 0.74. It was found that hybrid derived from crossing between parental inbred lines possessing broad genetic background would express high heterosis.